MANAGEMENT OF PULMONARY TUBERCULOSIS WITH DIABETES MELLITUS ON 52 YEARS OLD MALE PATIENT - Prayogi, Nirmala Astri (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Tuberculosis (TB) is an infectious lung disease which occurred most in many developing countries such as Indonesia and usually infect children and adults. According to Lampung Province data and health information, pulmonary tuberculosis case detection rate in Lampung in 2011 was 48.65 thousand inhabitants, while in 2012 fell to 24.12 thousand inhabitants. The increase in cases of TB in patients with diabetes mellitus (DM) also occurred in Indonesia. A lot of diabetic patients who had TB and it increased the morbidity and mortality of TB and DM. Treatment of pulmonary tuberculosis in patients with DM similar to patients with non-DM on the controlled blood sugar levels condition. A man, 52 years old, came with complaint of cough since 1 month ago. Cough was not accompanied by phlegm or blood. Patients also complain of cold sweat at night, weight loss of about 9 kilos in 1 month, nausea, and sometimes patients complaint of shortness breath. Patients have a neighbor who suffered tuberculosis and is currently undergoing treatment for TB. Since three years ago patient has been suffering from diabetes and blood sugar control diligently every month. On physical examination found blood pressure, pulse, respiration and temperature at normal limit. At pulmonary auscultation found any ronkhi (+) in both lung fields. Chest radiographs obtained TB diffuse, normal cor. Results of sputum smear was negative (-), random blood glucose levels of 180 mg/dl. Patients diagnosed with pulmonary tuberculosis accompanied with diabetes mellitus. Therapy was given in the form of RHZE combination pills and oral antidiabetic glibenclamide 1 x 5 mg and metformin 2 x 500 mg. [J Agromed Unila 2015; 2(1):6-12] Keywords: diabetes mellitus, treatment, tuberculosis